Developing Foundational Counseling Skills for Addressing Adherence Issues in Auditory Rehabilitation - Johnson, Carole E.; Jilla, Anna Marie; Danhauer, Jeffrey L. (Seminars in Hearing, 2018)
Successfully getting patients with confirmed hearing loss to use hearing aids is a major challenge for hearing health care professionals. Treatment adherence has been defined as the active involvement of patients in collaborating with health care providers to plan and manage treatment regimens. Counseling patients with hearing loss on adherence to recommendations of hearing aid uptake and utilization is dependent upon building a patient-centered therapeutic relationship during the initial diagnostic evaluation. The purpose of this article is to provide resources, tools, and engaging learning activities for training students on the development of a hierarchy of counseling skills: informational counseling (e.g., checking comprehension and problem clarification), communication skills (e.g., promotion of shared-communication space, congruence, listening with the third ear, unconditional positive regard, and empathy), and health behavior change (e.g., Motivational Interviewing and the Teach-Back Method) that are prerequisites for addressing treatment adherence.
Keywords: Audiology; counseling; treatment adherence; health behavior change